A afirmação incondicional da vida : vontade de potência e a inauguração de um novo modo de pensar - Mazia, Victor Hugo (2016)
In this paper, we investigate the Nietzsche project of affirmation of life. This project seems to have had a great relevance within the philosophy of Nietzsche, even if it has undergone some changes over the years. In The Birth of Tragedy (1872), the concept of affirmation of life appears in the form of aesthetic justification of existence, promoted by apollonian and dionysian impulses, which gives a metaphysical character to the work. As this work is concerned, Nietzsche assumes the reality of the Ur-ein, giving a metaphysical character to his theses. On the other hand, in Human, All Too Human (1878), Nietzsche criticizes all metaphysical thought. Later, in 1886, the philosopher wrote several prefaces to his previous work, listing their main problems and, from that, heading to life-affirming thoughts. At the same time, in Beyond Good and Evil (1886), Nietzsche shows how modern thought promotes a life denial culture. Based in this diagnosis, the German philosopher points out that the philosophers productions are symptoms of their impulsive or physiological configuration: the affirmation or denial of life as an ongoing process of self-overcoming indicates hierarchy (health) or disintegration (disease) of the impulses. Nietzsche proposes in this context a worldview based on the will to power, and thus aims to overcome metaphysics and their prejudices and therefore allow the appearance of an affirmation of life philosophy. We propose the pivotal role of the will to power in Nietzsche's more mature project of affirmation of life: it is the basis for several other notions, such as eternal return and amor fati.